Individualised submaximal shuttle run test - A comparison of elite and recreational athletes heart rate responses and relationships with fitness - Scott, T. J.; Caia, J.; Kelly, V. G. (Journal of Australian Strength and Conditioning, 2017)
Maximal exercise tests are an accepted method to monitor fitness, however given the exertion required to complete a maximal test, exposing an athlete to such assessment on a regular basis within a training setting seems inappropriate. Submaximal exercise tests may deliver a viable alternative for monitoring athletes physiological capabilities and responses to training, thus providing an appropriate tool to monitor athletes training status. It has been demonstrated that heart rate (HR) response to a given submaximal workload may differ depending on the level of fitness and training status. Typically, trained athletes will exhibit lower exercise heart rate (HRex) and faster heart rate recovery (HRR) rates than untrained or recreationally trained individuals. The purpose of this study was to compare elite and recreational athletes HR responses to an individualised submaximal shuttle run test (SSRIndiv) and examine the association of these results and levels of fitness.